Governance of Electronic Health Record Modification at U.S. Academic Medical Centers - Ravi, Akshay; Arvisais-Anhalt, Simone; Weia, Benjamin; Khanna, Raman; Adler-Milstein, Julia; Auerbach, Andrew (Applied Clinical Informatics, 2023)
Objectives A key aspect of electronic health record (EHR) governance involves the approach to EHR modification. We report a descriptive study to characterize EHR governance at academic medical centers (AMCs) across the United States.Methods We conducted interviews with the Chief Medical Information Officers of 18 AMCs about the process of EHR modification for standard requests. Recordings of the interviews were analyzed to identify categories within prespecified domains. Responses were then assigned to categories for each domain.Results At our AMCs, EHR requests were governed variably, with a similar number of sites using quantitative scoring systems (7, 38.9%), qualitative systems (5, 27.8%), or no scoring system (6, 33.3%). Two (11%) organizations formally review all requests for their impact on health equity. Although 14 (78%) organizations have trained physician builders/architects, their primary role was not for EHR build. Most commonly reported governance challenges included request volume (11, 61%), integrating diverse clinician input (3, 17%), and stakeholder buy-in (3, 17%). The slowest step in the process was clarifying end user requests (14, 78%). Few leaders had identified metrics for the success of EHR governance.Conclusion Governance approaches for managing EHR modification at AMCs are highly variable, which suggests ongoing efforts to balance EHR standardization and maintenance burden, while dealing with a high volume of requests. Developing metrics to capture the performance of governance and quantify problems may be a key step in identifying best practices.
Keywords: electronic health record; clinical governance; qualitative research; EHR governance